2021
DOI: 10.3389/fcell.2021.641469
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mechanisms of Tumor Therapy Resistance Driven by Tumor Microenvironment

Abstract: Cancer is a disease which frequently has a poor prognosis. Although multiple therapeutic strategies have been developed for various cancers, including chemotherapy, radiotherapy, and immunotherapy, resistance to these treatments frequently impedes the clinical outcomes. Besides the active resistance driven by genetic and epigenetic alterations in tumor cells, the tumor microenvironment (TME) has also been reported to be a crucial regulator in tumorigenesis, progression, and resistance. Here, we propose that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 368 publications
(443 reference statements)
2
81
0
Order By: Relevance
“…The tumor microenvironment (TM) is a crucial regulator of malignancy ( Wu et al, 2021 ). In particular, the tumor immune microenvironment, which reflects the immune status of the tumor tissues, performs critical functions, and has attracted increasing attention ( Pitt et al, 2016 ; Locy et al, 2018 ; Lei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TM) is a crucial regulator of malignancy ( Wu et al, 2021 ). In particular, the tumor immune microenvironment, which reflects the immune status of the tumor tissues, performs critical functions, and has attracted increasing attention ( Pitt et al, 2016 ; Locy et al, 2018 ; Lei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of immune infiltration have shown that the tumor immune microenvironment has a key role in cancer progression and affects the clinical outcomes of cancer patients (Murciano-Goroff et al, 2020;Zhang and Zhang, 2020). As immune cells are the cellular basis of immunotherapy, an in-depth understanding of immune infiltration in the tumor immune microenvironment can reveal underlying molecular mechanisms and provide new strategies to improve the efficacy of immunotherapy (Wu et al, 2021). A key result of the present work was that PER1 expression was closely related to the infiltration levels of a variety of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…A key control on the development of malignant tumors, which typically have poor prognosis, is the activation of invasion and metastasis, which acts in conjunction with three other hallmarks (sustained angiogenesis, evading immune response and tumor-promoting inflammation). It is now realized that the acquisition of these hallmarks is further controlled by contributions from the tumor microenvironment, consisting of the extracellular matrix [ 90 ], stromal cells and immune cells, but the precise dynamics between the nontumor microenvironment (NTME), tumor microenvironment (TME) [ 105 ] and the systemic immune system remains abstruse. A high-dimensional proteomic and transcriptomic approach was used to examine this in HCC.…”
Section: The Hallmarks Of Cancermentioning
confidence: 99%